Interdisciplinary Collaboration in Maternal Mental Health. Issue 4 (July 2017) - Selix, Nancy; Henshaw, Erin; Barrera, Alinne; Botcheva, Luba; Huie, Erin; Kaufman, Gabrielle
Abstract : Abstract: One out of every five to seven births is affected by postpartum depression, making it the most common maternal health problem in the first year after childbirth. Early identification and treatment are essential, though screening and treatment rates are low. Factors that inhibit effective screening and treatment include lack of uniform screening policies in all maternal health settings, poor coordination of care between primary care and mental health services, inadequate coordination of community education efforts and resources, social stigma surrounding mental health treatment, and ineffective application of research and technology in the clinical setting. An interdisciplinary model that includes primary care providers, mental health professionals, community resources, policy makers, researchers, and technological innovators addresses these gaps in care and enhances screening and treatment efforts that improve overall maternal and child health. We present a promising interdisciplinary cross-organizational approach coalescing diverse perspectives from those working across policy, research, training, primary care, and mental health in various disciplines to practice collaboratively to improve perinatal mental healthcare. Abstract : Creating an interdisciplinary approach for maternal mental health that includes professionals involved in policy, research, community advocacy, and clinical practice can improve access to care, streamline services, and improve maternal health outcomes. This article offers examples of interdisciplinary approaches that blend technology, education, research, policy, primary care, and mental health services and discusses their benefits and challenges for maternal mental health services.